Living Images and Marian Devotion: Words, Gestures, and Gazes - Murcia Nicolás, Fuensanta (Religions, 2023)
This article examines the living images of the Virgin through the illustration of one of the most important collections of miracles of the 13th century, Les Miracles de Nostre Dame by Gautier de Coinci. In this case, I will focus my attention on manuscript 551 of Besançon (Besançon, BM, MS 551), which, although it has many flaws in its manufacture, offers an interesting presentation of living images. The study of these miniatures reflects the importance of devotion, the set of gestures, words, and gazes, in the medieval spectator’s experience of Marian images. At a time when these images’ legitimacy as sacred objects was still being debated, the artists in this manuscript show their power without censorship, presenting them as if they were the Virgin herself.